Investigation of the feasiblity of employing a radial turbine for a utility-scale supercritical CO₂ power cycle. - El Samad, Tala (Cranfield University, 2020)
With the current growth rate of world population, comes a high demand on electric energy generation. Technological advancements in metallurgy, fuel conversion, heat transfer, and turbomachinery design allow the continuous dominating rule of fossil fuel energy resources and the expansion of non-renewable based power cycles. The challenges arising due to greenhouse gas emissions from fossil fuel combustion necessitate regulated policies to limit CO₂ emissions in particular. Design considerations and issues in power plants revolve around increasing efficiencies, reducing noise pollution and land footprint, while mitigating emissions. An example of advanced power configurations include the supercritical CO₂ cycle that has gained much interest in recent years due to its compact-size turbomachinery, increased efficiencies compared to other conventional steam or gas cycles, and its ability to be coupled with a wide range of heat sources. Another avant-garde technology is an oxy-combustion cycle that proves more favourable than the other carbon capture and storage routes of gasification and absorption. A proposed NET Power (Allam) cycle, which combines both technologies of using supercritical CO₂ conditions in an oxy-combustion gas-fired power plant, seems promising with claims of cycle efficiencies reaching 55%. However, the Allam cycle is still in a pre-mature phase due to the barriers that inhibit its full-scale development; challenges include the design of a high-pressure, high-temperature turbine which dictates cooling requirements, material considerations, and number of stages to name a few. A radial turbine, which generally has a simpler construction and fewer stages when compared to an axial turbine, is suggested as a superior candidate configuration for cycles of high fluid density. A thermodynamic analysis of a mid-range cycle similar to that proposed by NET Power is established while lowering the turbine inlet temperature to 900 C in order to remove cooling complications within the radial turbine passages. The cycle conditions are then considered for the design of a 100 MWth power scale turbine by using preliminary and higher fidelity methods. Two radial turbine designs are illustrated; the first, whilst not satisfying the cycle operating conditions, is used to showcase the detailed 1D design as well as the 2D and 3D analyses procedures followed during this work. A second 510 mm diameter turbine, running at 21,409 rpm, capable of operating within a 5% range of the required cycle conditions, is designed and presented. Results from computational fluid dynamics simulations indicate the loss mechanisms responsible for the low-end value of the turbine total-to-total efficiency which is 69.87%. Mechanical stress calculations show that the aerodynamic flow path of the rotor blades experience tolerable stress values, however a more detailed disc design is required to meet actual material constraints.
Keywords: Thermodynamic analysis; mid-range cycle; radial turbine; computational fluid dynamics; simulations; mechanical stress